(untitled) (Educational Dimension, 2022)
Augmented reality is currently one of the most rapidly emerging technologies, with applications in the field of education. AR technology, according to a review of numerous publications, provides new options for teachers and makes learning more appealing to pupils of all ages. Students can use mobile AR apps to observe a real-world environment with virtual things layered or composited on top of it. This is especially true for young children. The article highlights the activities that allow a child to have a unique AR experience. There is a comparison of available augmented reality (AR) applications for learning the alphabet. The author describes a novel augmented reality application that was created with Unity, C#, and Vuforia. The developed mobile AR application allows students to learn the Ukrainian alphabet, number names, and animal sounds. The learning process is enhanced by three-dimensional visualization and sounding of each letter and number thanks to this program. An analysis of a survey of teachers and parents found that utilizing an AR application greatly boosted children’s motivation and self-efficacy in learning letters and numbers. The AR application aided in the retention of the child’s attention while learning new content by speeding up the process of memorization.